Strategies and Solutions in Overcoming the Challenges of Lipase Utilization in Biodiesel Production: A Review - Aulia, Cindy; Lase, Yuyun Krisdayanti; Annisa, Lutfillah Dini; Putri, Sauza Shafa Salsabila; Saputri, Dhista Dwi; Arif, Moh. Syaiful; Marliana, Eva Syaiful (Jurnal Beta Kimia, 2025)
Biodiesel production using lipase as a catalyst offers a more environmentally friendly approach compared to chemical catalysts. However, the application of lipase in industry still faces various challenges, such as high production costs, low enzyme stability, and longer reaction times. To address these constraints, various strategies have been developed. This review not only summarizes these strategies but also highlights recent approaches that are less commonly discussed in the literature, such as the use of non-alcohol routes with methyl acetate and the application of ultrasonic technology to improve conversion efficiency. Additionally, this review provides a fresh perspective by systematically comparing the effectiveness of various lipase immobilization methods and low-cost lipase sources. The uniqueness of this study lies in the comprehensive integration of conventional biocatalysis strategies and emerging innovative approaches. It is hoped that this approach will offer more practical and relevant guidance for the development of enzyme-based biodiesel production technologies, making lipase-based biodiesel production more efficient, economical, and sustainable, while contributing to the reduction of dependency on fossil fuels and the advancement of renewable energy.